The Teacher Within Contemporary Educational Reality. Manager, Bureaucrat or Citizen? - Astrid Męczkowska-Christiansen (University of Lower Silesia, 2015)
The article presents reflections on the role of the teacher in contemporary social reality dominated by neoliberal culture, which involves weakening democratic institutions; a corporate model of functioning in educational institutions; managerial discourse that reduces educational processes to management strategies; and the development of bureaucracy as a governance model. It is argued that "bureaucrat" and "manager" are the two versions of a professional role currently being imposed on teachers, as well as the antithesis of teachers' civic roles.